Mengatasi Kecemasan Pasien Selama Tindakan Pencabutan Gigi: Pendekatan dan Strategi Efektif - Amirah Maritsa; Hasrini Hasrini; Zahrawi Astrie Ahkam; Faradillah Usman; Suciyati Sundu (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2023)
Patient anxiety during tooth extraction is a common challenge in dental practice that can affect patient experience and outcome of the procedure. This study aimed to evaluate the effectiveness of approaches and strategies to address patient anxiety during tooth extraction procedures. Through counseling designed to improve patient understanding of the causes of anxiety, relaxation skills, and communication with the dentist, this study measured its impact on patient anxiety levels and preparedness. The study involved patients undergoing tooth extraction procedures, where they attended a counseling session that included information on factors that cause anxiety, breathing relaxation techniques, and communication skills. Data were collected before and after the counseling through a survey that assessed patient knowledge, ability to apply relaxation techniques, self-confidence, and anxiety levels. The results showed a significant increase in patient understanding of the causes of anxiety from 50% to 85%, ability to apply relaxation techniques from 30% to 75%, and self-confidence in facing the procedure from 40% to 80%. In addition, the ability to communicate with the dentist increased from 45% to 78%, and anxiety levels decreased from 70% to 40%. These findings confirm that an educational approach is effective in reducing patient anxiety, increasing preparedness, and improving the experience during tooth extraction. This strategy can be implemented widely to improve the quality of care and patient well-being in dental practice.